2001
DOI: 10.1254/jjp.85.339
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology of T-type Ca2+ Channels

Abstract: ABSTRACT-Over the past few years increasing attention has been focused on T-type calcium channels and their possible physiological and pathophysiological roles. Efforts toward elucidating the exact role(s) of these calcium channels have been hampered by the lack of T-type specific antagonists, resulting in the subsequent use of less selective calcium channel antagonists. In addition, the activity of these blockers often varies with cell or tissue type, as well as recording conditions. This review summarizes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 82 publications
(52 reference statements)
3
81
0
1
Order By: Relevance
“…These data suggest that the voltage-gated L-type Ca 2+ -channels are playing the major role in the generation of plateau potentials. Alternatively, nifedipine has an ability to inhibit T-type Ca 2+ -channels at 1 µM concentration, although this does not seem to be supported from the molecular pharmacology of Ca 2+ -channels (Mori et al, 1996;Heady et al, 2001). In summary, the effects of nifedipine and Ni 2+ on plateau potentials generated in submucosal ICC of the mouse proximal colon indicated that at subthreshold concentrations, Ni 2+ reduces the rate of rise of the initial component and nifedipine reduced the duration of the plateau component.…”
Section: Discussionmentioning
confidence: 94%
“…These data suggest that the voltage-gated L-type Ca 2+ -channels are playing the major role in the generation of plateau potentials. Alternatively, nifedipine has an ability to inhibit T-type Ca 2+ -channels at 1 µM concentration, although this does not seem to be supported from the molecular pharmacology of Ca 2+ -channels (Mori et al, 1996;Heady et al, 2001). In summary, the effects of nifedipine and Ni 2+ on plateau potentials generated in submucosal ICC of the mouse proximal colon indicated that at subthreshold concentrations, Ni 2+ reduces the rate of rise of the initial component and nifedipine reduced the duration of the plateau component.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, there are no highly selective drugs or peptide toxins (369) that selectively block Ca v 3 channels. A comprehensive review of drugs tested on native T-type channels was recently published (158); therefore, this review focuses on drugs whose mechanism may involve block of T-type channels.…”
Section: Pharmacologymentioning
confidence: 99%
“…Subsequent studies required much higher concentrations for block (IC 50 ϳ200 M; reviewed in Ref. 158). Recombinant T-type channels can be totally blocked by octanol, with 50% inhibition occurring at 160 M for Ca v 3.1 and 219 M for Ca v 3.2 (404).…”
Section: Anestheticsmentioning
confidence: 99%
“…Finally, selectivity of T-type VGCC blockers may account for the protective effects of trimethadione and ethosuximide. Recent studies have suggested that the blocking of ionic channels other than T-type VGCC is relevant to the antiepileptic actions of ethosuximide because most studies failed to confirm the blocking of T-type currents at therapeutically relevant concentrations of ethosuximide (Heady et al 2001). Unfortunately, no compounds that are selective for T-type VGCC have been identified so far; thus, it is uncertain whether the selective inhibition of T-type VGCC is of clinical importance in acoustic injury.…”
Section: +mentioning
confidence: 99%